"It's your turn to step into their shoes": The role of empathy in adolescents experiencing maternal cancer. (14th May 2019) - Rodriguez, Leonor; Dolan, Pat
Abstract : Purpose: The purpose of this paper is to evaluate the role of empathy in adolescents coping with maternal cancer to identify passive and active empathy forms and the role of these in adolescent coping at a challenging time. Design/methodology/approach: This study was a secondary content analysis carried out on 15 adolescent interviews that were analysed to find the evidence of empathy in active and passive forms. Adolescents were between 14 and 20 years of age, their mothers were diagnosed with cancer in the previous 24 months to the interview. Findings: The analysis identified more evidence of active forms of empathy than passive directed at ill mothers and their families as helpful behaviours and emotional support. Passive empathy was experienced by adolescents who did not have major changes in their daily routines because of maternal cancer. Both passive and active empathy were perceived as coping mechanisms. Maternal illness motivated adolescents' empathy and encouraged actions to support their mothers, immediate and extended families. Originality/value: Empathy is complex but can be important for adolescent development including their social skills and relationships; however, research has not evaluated the role of empathy in adolescents experiencing maternal cancer.